(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Sensor applications have a serious influence on everyday objects that improve the human quality of life. Key topics should be soil biological sensing, crop production and post-harvest implementation. Topics associated with soil sensing involve soil content control, sewage systems and soil erosion movement paths when harrowing, while seedling detection issues involve assessment of winery spray drift applications, implementations ofwinter wetland thermal imaging, forest wellness systems and remotely sensed applications.